Ulrich von Liechtenstein's "Service of Ladies" - Thomas, J.W (UNC Studies in the Germanic Languages and Literatures, 1969)
This volume presents the first English translation of one of the most original literary products of the German medieval period. It is introduced with a sketch of the poet's life, an evaluation of his work as autobiography and as fiction, and a survey of the extensive criticism that has been devoted to it. "Service of Ladies" has been put into English not only as a significant document of its time and place, but more especially because it is a piece of literature which is perhaps as entertaining today as it was seven centuries ago when Ulrich was reciting it to the laughter and applause of the knights and ladies of his native Styria.